Environment, media, and popular culture in Southeast Asia - Telles, Jason Paolo; Ryan, John (John Charles) (Poet); Dreisbach, Jeconiah Louis (Singapore Springer Nature Singapore Pte Ltd., 2022)
This book addresses the increasingly important subject of ecomedia by critically examining the interconnections between environment, ecology, media forms, and popular culture in the Southeast Asian region, exploring methods such as textual analysis, thematic analysis, content analysis, participatory ethnography, auto ethnography, and semi-structured interviewing. It is divided into four sections: I. Activism, Environm7ent, and Indigeneity; II. Political, Ecologies and Urban Spaces; III. Narratives, Discourses, and Aesthetics; and IV. Imperialism, Nationalism, and Islands, covering topics such as broadcast media (radio and TV) and the environment; green cinema and ecodocumentaries, ecodigital art, digital environmental literature. It is of great interest to researchers, students, practitioners and scholars working in the area of humanities, media, communications, cultural studies, environmental humanities, environmental studies, and sustainability.
Chapter 1. Introduction: Environment, media, and popular culture in Southeast Asia / John Charles Ryan and Jason Paolo Telles -- Part 1. Activism, Indigeneity, and the sacred -- Chapter 2. Sons of Soil: Reconstituting Bumiputeraism Indigeneity, Tanah Melayu, and Tanah Adat Orang Asli (Yvonne Tan) -- Chapter 3. Reading the Novel Sarongge through the Eyes of Female Environmental Activists in Indonesia (Meredian Alam) -- Chapter 4. Nguyen Trinh This Ecocinema: An Artistic Response to Environmental Problems in Vietnam (Tran Ngoc Hieu) -- Chapter 5. Vietnamese Cinema and Ecological Issues: The Story of Pao and Black Forest (Le Thi Dng) -- Chapter 6. "Greatest Prodigy of the Vegetable World" : The Mediation of Rafflesia, the Corpse Flower of Southeast Asia (John Charles Ryan) -- Part 2. Political Ecologies and Urban Spaces -- Chapter 7. The Nightcrawlers and the Optics of Death: Documenting Dutertes Necro-Politics (Jose Kervin Calabias) -- Chapter 8. Intervening in the Indonesian Election through Ecodocumentary: The Case of Sexy Killers (Agung Wardana) -- Chapter 9. The Village as a Space of Rights: The Political Ecology of Mangroves and Fish Farming in an Island Village in Central Philippines (Eulalio Guieb) -- Chapter 10. The West Philippine Sea Dispute and Memefied Fish on Facebook (Jason Paolo Telles) -- Chapter 11. Telegraphic Poetics in Anxiety Myths by Afrizal Malna: Re-envisioning Human Interconnection with Material Ambience in the Digital Millennium (Henrikus Joko Yulianto) -- Part 3. Narratives, Discourses, and Aesthetics -- Chapter 12. Against DomiNation: Intersectional Aesthetics in U. Raksasad's Fictional Documentary Agrarian Utopia (Natalie Boheler) -- Chapter 13. The Littoral Zone as Guerilla Zone: The Hydroaesthetics of Revolutionary Music for Filipino Fisherfolk (Jose Monfred Sy) -- Chapter 14. Maps and Shifting Power Relations in the Mekong Delta Region (Tami Banh) -- Chapter 15. The Trend of "Movies as Tourism Promotion" : From Picturesque Landscapes to Eco-Consciousness (Hoang Cam Giang) -- Chapter 16. The Reporting of Climate-Related News by the National Broadcast Media of Brunei Darussalam (Sharifah Nurulhuda Alkaff) -- Chapter 17.Ecocentric Underpinnings in the My Village Children's TV Program in Laos (Jason Paolo Telles) -- Part 4. Imperialism, Nationalism, and Islands -- Chapter 18. Singapore, Colonialism, and the Environment (Marcella Polain) -- Chapter 19. Archipelagic Choreography: Movement and Intertwining Bodies in Emiliana Kampilans Dead Balagtas (Maria Karaan) -- Chapter 20. National Properties, National Ecologies: Postcolonial and Ecocritical Engagements with Mikhail Reds Birdshot (2016) (Trish Remetir) -- Chapter 21. Wild Honey: Caring for Bees in a Divided Land (Balthasar Kehi) -- Chapter 22. Slow Cinema, Filipino Epistemology, and Nature in Lav Diazs From What Is Before (Stefan Torralba) -- Chapter 23. Escaping Paradise, Returning this Island: Examining Representations of Siargao and Islandic Space (Leonard Thomas Shaw)
Includes bibliographical references.
Keywords: Communication in the environmental sciences -- Southeast Asia; Environmental sciences; Ecocriticism -- Southeast Asia